Amending Miller's Pyramid to Include Professional Identity Formation - Cruess, Richard L; Cruess, Sylvia R; Steinert, Yvonne (Academic medicine, 2016)
In 1990, George Miller published an article entitled "The Assessment of Clinical Skills/Competence/Performance" that had an immediate and lasting impact on medical education. In his classic article, he stated that no single method of assessment could encompass the intricacies and complexities of medical practice. To provide a structured approach to the assessment of medical competence, he proposed a pyramidal structure with four levels, each of which required specific methods of assessment. As is well known, the layers are "Knows," "Knows How," "Shows How," and "Does." Miller's pyramid has guided assessment since its introduction; it has also been used to assist in the assessment of professionalism.The recent emphasis on professional identity formation has raised questions about the appropriateness of "Does" as the highest level of aspiration. It is believed that a more reliable indicator of professional behavior is the incorporation of the values and attitudes of the professional into the identity of the aspiring physician. It is therefore proposed that a fifth level be added at the apex of the pyramid. This level, reflecting the presence of a professional identity, should be "Is," and methods of assessing progress toward a professional identity and the nature of the identity in formation should be guided by currently available methods.